A quantitative ring recovery analysis of migration in European Water Rails Rallus aquaticus - Lugg, Kristin; Bakken, Vidar; Lislevand, Terje (Ornis Norvegica, 2018)
The Water Rail Rallus aquaticus is generally regarded as a facultative migrant in which migration patterns vary geographically. However, quantitative analyses of migration directions and how migration distances vary across Europe are hitherto lacking. We analysed recoveries of Water Rails ringed in Europe and tested for a general migration direction in this material. From previous literature descriptions we predicted birds to migrate farther the longer north and east they breed. More than half of the birds included in the data set were ringed in Germany (48%) and Hungary (12%) and most winter recoveries came from SW coastal Europe. We found that the migratory direction in autumn was strongly oriented towards SW with no effect of latitude or longitude of the breeding site. There were no differences in migration direction between old (2Y+) and young (1Y) birds, or between males and females, although sample sizes were admittedly small in the latter comparison. As predicted, migration distances were positively correlated with both latitude and longitude of breeding sites. We encourage more trapping and ringing of Water Rails breeding and wintering across Europe in order to improve the ring recovery data. The use of modern tracking devices like light-level geolocators also has a high potential of improving our understanding of migratory ecology in this secretive species.